Genome-wide significant predictors of metabolites in the one-carbon metabolism pathway - Hazra, Aditi; Kraft, Peter; Lazarus, Ross; Chen, Constance; Chanock, Stephen J; Jacques, Paul; Selhub, Jacob; Hunter, David J (Human molecular genetics, 2009)
Low plasma B-vitamin levels and elevated homocysteine have been associated with cancer, cardiovascular disease and neurodegenerative disorders. Common variants in FUT2 on chromosome 19q13 were associated with plasma vitamin B12 levels among women in a genome-wide association study in the Nurses' Health Study (NHS) NCI-Cancer Genetic Markers of Susceptibility (CGEMS) project. To identify additional loci associated with plasma vitamin B12, homocysteine, folate and vitamin B6 (active form pyridoxal 5'-phosphate, PLP), we conducted a meta-analysis of three GWA scans (total n = 4763, consisting of 1658 women in NHS-CGEMS, 1647 women in Framingham-SNP-Health Association Resource (SHARe) and 1458 men in SHARe). On chromosome 19q13, we confirm the association of plasma vitamin B12 with rs602662 and rs492602 (P-value = 1.83 x 10(-15) and 1.30 x 10(-14), respectively) in strong linkage disequilibrium (LD) with rs601338 (P = 6.92 x 10(-15)), the FUT2 W143X nonsense mutation. We identified additional genome-wide significant loci for plasma vitamin B12 on chromosomes 6p21 (P = 4.05 x 10(-08)), 10p12 (P-value=2.87 x 10(-9)) and 11q11 (P-value=2.25 x 10(-10)) in genes with biological relevance. We confirm the association of the well-studied functional candidate SNP 5,10-methylene tetrahydrofolate reductase (MTHFR) Ala222Val (dbSNP ID: rs1801133; P-value=1.27 x 10(-8)), on chromosome 1p36 with plasma homocysteine and identify an additional genome-wide significant locus on chromosome 9q22 (P-value=2.06 x 10(-8)) associated with plasma homocysteine. We also identified genome-wide associations with variants on chromosome 1p36 with plasma PLP (P-value=1.40 x 10(-15)). Genome-wide significant loci were not identified for plasma folate. These data reveal new biological candidates and confirm prior candidate genes for plasma homocysteine, plasma vitamin B12 and plasma PLP.